Hvarska renesansna intelektualna polja - Čavić, Aldo (2020)
Dalmatian communes in the fifteenth century were discrete political organisms, structured as aristocratic republics, whose inhabitants felt their commune to be their only homeland. There existed, however, a wider social space, the foundation of whose process of integration was based on people, their relationships and the proximity of the structures of their belief systems, which can be divided into a larger, so-called „Adriatic social space” which is achieved over the whole of the Adriatic, both the Croatian and Italian portions, and the narrower „Eastern Adriatic”, in the land of the Schiavona, created by their intellectual activities, relationships and the communication between the nobility from the Dalmatian communes, most evident in the creation of the space of humanist and renaissance literature, the space of the Dalmatian res publice litterarie. This „literary republic” exceeded the narrow borders of the communes, the domovina, and also the class divisions inside the commune, as both noble and popular authors participated in it. Like all republics, among the members existed a hierarchical ladder with roles played by specific members of the „republic”. This social space of the Dalmatian literary republic is researched in light of the theories of French sociologist and philosopher Pierre Bourdieu on intellectual and cultural fields, proceeding from the premise that behind each act of intellectual and artistic creation there lies a hidden relation between the creator and his work, conditioned by the social connections among which the acts of creation and communication are upheld, that is to say, the work itself is conditioned by the position of the creator in his intellectual field. In this paper, 47 communicative texts, for the most part epistles, dating up to the 1570s are analyzed, whose senders or receivers were Croatian authors.
Bibliografske bilješke uz tekst ; bibliografija: str. 92-94.
Sažetak ; Summary.
Keywords: Renesansa -- Književnici -- Poslanice -- Intelektualna povijest; Hvar